Low-modulus high-elasticity OCA optical pressure-sensitive adhesive and preparation method thereof

The four-block copolymer is prepared by using the reversible addition fracture chain transfer emulsion polymerization method in OCA optical pressure-sensitive adhesive, and the monomer type and molecular weight of the tail block copolymer are regulated, so the low modulus and high elasticity characteristics are achieved, and the solution is solved. The lack of performance problems of traditional OCA optical pressure-sensitive adhesives in high-end applications have been achieved, and efficient bonding performance is achieved for flexible display devices.

CN119432273APending Publication Date: 2025-02-14HANGZHOU ENTRON MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311847401.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Traditional OCA optical pressure sensitive adhesives may cause bending or stress accumulation of optical components during assembly, and low-modulus optical adhesives have low resilience, resulting in problems such as creep, wrinkles and creases, making it difficult to be used in high-end fold-resistant display applications. Meet the needs.

Method used

The four-block copolymer is prepared by reversible addition fracture chain transfer emulsion polymerization method. By regulating the monomer type and molecular weight of the tail block copolymer, the low modulus and high elastic properties of OCA optical pressure-sensitive adhesive are achieved, and by increasing the The soft monomer section increases the peel strength.

Benefits of technology

It realizes the low modulus and high elasticity characteristics of OCA optical pressure-sensitive adhesive, improves peel strength, and is suitable for flexible display devices, solving the insufficient performance problem of traditional OCA optical pressure-sensitive adhesive in high-end applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432273A_ABST
    Figure CN119432273A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, and discloses a low-modulus high-elasticity OCA optical pressure-sensitive adhesive and a preparation method thereof. The preparation method of the OCA optical pressure-sensitive adhesive comprises the following steps: dissolving raw materials containing a tetrablock copolymer, tackifying resin and an auxiliary agent in a dispersion medium, coating to form a film, and drying to obtain the OCA optical pressure-sensitive adhesive, the structural general formula of the tetrablock copolymer is M1-b-M2-b-M3-b-M4, M1 and M3 are from hard monomers, and M2 and M4 are from soft monomers; the mass ratio of a hard monomer in the comonomer is 10-30%, the mass ratio of a soft monomer is 70-90%, and the mass ratio of M4 is greater than 0%. According to the tetrablock copolymer, reversible addition fragmentation chain transfer emulsion polymerization controllable design is adopted to prepare the tetrablock copolymer, and the modulus can be greatly reduced and the peel strength can be improved on the basis of not influencing the rebound resilience by regulating and controlling the monomer type, molecular weight and the like of the tail end block copolymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to an OCA optical pressure-sensitive adhesive with low modulus and high elasticity and a preparation method thereof. Background Art

[0002] Optically clear adhesive (OCA) is a key material widely used in optical components and display technology. Its performance has an important impact on ensuring the quality and performance of optical components. OCA is usually used to bond and fix optical components such as liquid crystal displays (LCDs) and organic light-emitting diodes (OLEDs). In these applications, OCA not only needs to have excellent optical properties, but also needs to meet the requirements of mechanical properties, adhesion properties, and environmental stability.

[0003] However, traditional OCA optical pressure-sensitive adhesives may have some problems in some cases. High-modulus OCA may cause bending or stress accumulation of optical components during assembly, thereby reducing the accuracy and stability of assembly. Low-modulus OCA can better adapt to the deformation of optical components and reduce the loss of optical performance caused by deformation. However, low-modulus optical adhesives often have low resilience, which can cause the OCA optical adhesive to creep and visually cause wrinkles and creases. Therefore, the development of a low-modulus and high-elasticity OCA optical pressure-sensitive adhesive has important practical application value.

[0004] On the other hand, when preparing low modulus and high elasticity OCA optical pressure-sensitive adhesive, many factors need to be considered. For example, the composition of the material, the selection of the cross-linking agent, the polymerization process conditions, etc. will affect the final performance. Therefore, in order to prepare a method for preparing a low modulus and high elasticity OCA optical pressure-sensitive adhesive, it is necessary to regulate the mechanical properties of the material while maintaining excellent optical properties to meet the needs of practical applications.

[0005] At present, most OCA optical pressure-sensitive adhesives are prepared by UV light-curing polymerization. They often increase the concentration of initiators and then increase the cross-linking density, thereby improving the elasticity of OCA optical pressure-sensitive adhesives. However, the key difficulty lies in the inability to achieve a balance between fluidity and elasticity. The modulus of OCA optical pressure-sensitive adhesives will be significantly improved, and the tensile properties will deteriorate, making it difficult to apply to foldable screen mobile phones.

[0006] For example, CN117025136A discloses a high-performance UV-curable OCA adhesive and film, which includes the following raw material components by weight: 80-120 parts of prepolymer, 0.01-1 parts of initiator, and 0.01-1 parts of auxiliary agent; the prepolymer is obtained by mixing monomers with prepolymer initiators and then performing prepolymerization reaction under ultraviolet irradiation, and the monomers include at least two of hard monomers, soft monomers, and functional monomers. The present invention provides a high-performance UV-curable OCA adhesive and film, which can maintain high creep recovery and excellent bonding strength while taking into account high-temperature storage modulus (storage modulus>30kpa at 80°C), has the advantages of wide application range, high bonding strength to various materials, good flexibility, etc., and has good application prospects.

[0007] In addition, OCA optical adhesive can also be prepared by emulsion polymerization, which often adjusts the modulus of the optical adhesive by adding diblock copolymers and homopolymers, while maintaining resilience, CN 115260921 A discloses an OCA optical pressure-sensitive adhesive and a preparation method thereof, which is composed of one or more block copolymers. The method adopts reversible addition-fragmentation chain transfer emulsion polymerization, and by controlling the monomer type and the feeding order, a controllable design is used to prepare a block copolymer, and the prepared one or more block copolymers are mixed, and the OCA optical pressure-sensitive adhesive is prepared by solution film forming. It has the advantages of high tensile strength, high transparency and low haze. But its modulus is still not low enough, and its disclosed optical adhesive Young's modulus is 162.7KPa, and then in actual high-end folding display applications, a further lower modulus is often required, for example, less than 130kPa.

[0008] Therefore, it is an urgent need in the field of optical devices to produce OCA optical pressure-sensitive adhesives with lower modulus and high elasticity through simple methods, so as to achieve better performance and application effects in the application field of optical components. Summary of the invention

[0009] Aiming at the problem that low modulus and high elasticity of OCA optical pressure-sensitive adhesive cannot be achieved at the same time, the present invention provides a structure-controllable low modulus and high elasticity OCA optical pressure-sensitive adhesive, adopts controllable design of reversible addition-fragmentation chain transfer emulsion polymerization to prepare tetrablock copolymers, and regulates the monomer type and molecular weight of the tail block copolymer, so as to reduce the modulus and improve the peel strength to a greater extent without affecting the rebound elasticity.

[0010] To achieve the above object, the technical solution adopted by the present invention is:

[0011] A low modulus and high elasticity OCA optical pressure-sensitive adhesive, the preparation of which comprises the steps of: dissolving a raw material containing a tetrablock copolymer, a tackifying resin and an auxiliary agent in a dispersion medium, coating to form a film and then drying to obtain the result;

[0012] The general structural formula of the tetrablock copolymer is M1-b-M2-b-M3-b-M4, wherein M1, M2, M3, and M4 are comonomers in the block copolymer, M1 and M3 are from hard monomers, and M2 and M4 are from soft monomers; the mass proportion of the hard monomer in the comonomer is 3-30%, and the mass proportion of the soft monomer is 70-90%; the mass proportion of M4 in the comonomer is greater than 0%, preferably greater than 5%.

[0013] The present invention adopts RAFT emulsion polymerization for preparation. By adding soft monomers in the tail section, on the one hand, the last soft section is connected to the first three sections. Compared with the blending of triblock copolymers and homopolymers, the optical adhesive prepared by the present invention has stronger cohesion, and will not cause the optical adhesive to have residual adhesive when performing a peeling test, so that the pressure-sensitive adhesive can be used normally. On the other hand, compared with the blending of triblock copolymers and diblock copolymers, the addition of diblock copolymers will increase the addition of hard monomers, thereby causing the modulus to decrease less than that of directly preparing a tetrablock copolymer.

[0014] The number average molecular weight of the tetrablock copolymer is 800,000 to 800,000 g / mol, of which the number average molecular weight of the block formed by M4 is 100,000 to 200,000 g / mol, and the number average molecular weight of the block formed by M4 is 100,000 to 200,000 g / mol. M4 needs to have a sufficient molecular weight to ensure a significant decrease in the modulus, so that the modulus of the copolymer can be reduced to 130 kPa or lower.

[0015] The hard monomers include one or more of styrene, methyl acrylate, methyl methacrylate, acrylamide, methacrylic acid, acrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, acrylonitrile and vinyl acetate, and the glass transition temperature of the blend is in the range of 60 to 150°C.

[0016] The soft monomer includes one or more of 2-propylheptyl acrylate, octyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, isooctyl acrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, isooctyl methacrylate, butadiene, isoprene, methacrylic acid, acrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, ethylene-butene and methacrylic acid, and the glass transition temperature of the blend ranges from -90 to -30°C.

[0017] Preferably, the hard monomer includes one or more of styrene, acrylic acid, and acrylamide.

[0018] Preferably, the soft monomer includes one or more of 2-propylheptyl acrylate, isooctyl acrylate, and n-butyl acrylate.

[0019] The mass proportion of M1 in the comonomer is 2-15%, the mass proportion of M2 is 30-90%, the mass proportion of M3 is 2-15%, and the mass proportion of M4 is greater than 0% and less than 60%;

[0020] Preferably, in the comonomer, M1 accounts for 2-7% by weight, M2 accounts for 30-70% by weight, M3 accounts for 2-7% by weight, and M4 accounts for 20-60% by weight;

[0021] Further preferably, the mass proportion of M2 is 30-50%, and the mass proportion of M4 is 40-60%; wherein the higher the M4 content, the lower the modulus of the final copolymer, but when it is too high, the synthesis efficiency of the polymer will be reduced, resulting in the inability to synthesize some monomers, causing an increase in cost.

[0022] The tackifying resin includes any one or more of T-801, T-801L, 900L, 901L, TP2019 and 803L;

[0023] The other additives are any one or more of antioxidants, ultraviolet light absorbers, anti-ultraviolet additives and inks; within the wavelength range of 300-800nm, the OCA optical pressure-sensitive adhesive has a light transmittance of more than 90% and a haze of less than 1%.

[0024] The dispersion medium includes any one of diethyl ether, methyl tert-butyl ether, tetrahydrofuran, methyl ethyl ketone, ethyl acetate and methyl propionate.

[0025] The present invention also provides a method for preparing the low modulus and high elasticity OCA optical pressure-sensitive adhesive, comprising the steps of:

[0026] (1) dissolving an amphiphilic macromolecular reversible addition-fragmentation chain transfer agent in water, adding a first monomer, mixing, and then adding a first initiator to react for 1-3 hours to obtain a latex formed by a homopolymer;

[0027] (2) adjusting the pH of the latex in step 1 to 6.0-12.0, adding the second monomer, water and the second initiator thereto, reacting for 2-6 hours in an anaerobic environment, then adding the first monomer, reacting for 2-6 hours in an anaerobic environment, continuing to add the second initiator and the second monomer, and continuing to react for 2-6 hours in an anaerobic environment to obtain a polymer latex;

[0028] (3) mixing the polymer latex, hydrogen peroxide and hydrochloric acid for reaction for 1.5-3 hours, washing and drying the precipitated product to obtain a tetrablock copolymer;

[0029] (4) dissolving the tetrablock copolymer, tackifying resin and auxiliary agent in a dispersion medium, coating to form a film in an inert gas environment, and drying to obtain the OCA optical adhesive.

[0030] The reaction temperature in step 1 is 40-90°C; the reaction temperature in step 2 is 40-60°C; the reaction temperature in step 3 is 40-90°C;

[0031] In step 3, the hydrogen peroxide is an aqueous solution with a mass concentration of 20-40wt%, the hydrochloric acid is an aqueous solution with a mass concentration of 5-10wt%, and the volume ratio of the polymer latex, the hydrogen peroxide aqueous solution and the hydrochloric acid aqueous solution is 1:(1-5):(1-5).

[0032] The chemical structural formula of the amphiphilic macromolecular reversible addition fragmentation chain transfer agent (RAFT agent) is: R-(X n1 -bY n2 )-Z; wherein R is isopropanoyl, acetic acid, 2-cyanoacetic acid or 2-aminoacetic acid; X n1 In the formula, X is a methacrylic acid monomer or an acrylic acid monomer unit, n1 is the average polymerization degree of X, and n1 ranges from 10 to 30; Y n2 Y is a styrene monomer, n-butyl acrylate monomer, methyl acrylate, isooctyl acrylate or methyl methacrylate monomer unit, n2 is the average polymerization degree of Y, and n2 ranges from 1 to 8; Z is an alkyl dithioester group or an alkyl trithioester group.

[0033] The amount of RAFT agent added is 0.1-1.0 wt% of the mass of all comonomers.

[0034] The first initiator is any one of ammonium persulfate, potassium persulfate, hydrogen peroxide and a hydrogen peroxide derivative; and its mass is 1 / 2-1 / 30 of that of the RAFT agent.

[0035] The second initiator is any one of azobisisobutylimidazoline hydrochloride, azobisisobutylamidine hydrochloride, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, sodium hydrogen persulfate / potassium persulfate redox initiator and sodium persulfate / ammonium persulfate redox initiator. The mass dosage is 1 / 2-1 / 30 of that of the macromolecular RAFT agent.

[0036] The OCA optical pressure-sensitive adhesive comprises, by weight, 20 to 100% of a tetrablock copolymer, 0 to 30% of a tackifying resin and 0 to 30% of an auxiliary agent.

[0037] The auxiliary agent includes one or more common auxiliary agents such as IRGANOX 1726, IRGANOX 1010, and IRGANOX 1076 of BASF of Germany.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The optical pressure-sensitive adhesive prepared by the tetrablock copolymer in the present invention utilizes the structure of hard monomer-soft monomer-hard monomer-soft monomer. Compared with the triblock copolymer, a soft monomer with a free active chain is added at the end, so that the final pressure-sensitive adhesive has a lower modulus and higher resilience, and has a high peel strength.

[0040] (2) The preparation process of the tetrablock copolymer in the present invention is to prepare the tetrablock copolymer by a one-pot method of reversible addition-fragmentation chain transfer emulsion polymerization, thereby achieving precise control of the complex structure and making the preparation process simpler.

[0041] (3) The optical pressure-sensitive adhesive prepared in the present invention can reduce the modulus of the OCA optical adhesive by regulating the tail copolymer in the tetrablock copolymer, and the rebound resilience can exceed 95%, which is more suitable for its application in flexible display devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 : is the GPC curve chart of each stage of the tetrablock copolymer obtained in Example 1.

[0043] Figure 2 3 is a mechanical tensile curve of the tetrablock copolymer 1 obtained in Example 1.

[0044] Figure 3 It is a stress relaxation recovery curve diagram of the OCA optical pressure-sensitive adhesive obtained in Examples 1-3 and Comparative Example 1.

[0045] Figure 4 It is a graph showing the shear dynamic mechanical properties of the OCA optical pressure-sensitive adhesives obtained in Examples 1-3 and Comparative Example 1.

[0046] Figure 5 It is a graph showing the peel strength results of the OCA optical pressure-sensitive adhesive obtained in Examples 1-3 and Comparative Example 1. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0048] The raw materials used in the following specific embodiments are all purchased from the market.

[0049] Example 1

[0050] An optical pressure-sensitive adhesive prepared by using a poly(styrene-b-isooctyl acrylate-b-styrene-b-isooctyl acrylate) block copolymer, wherein the block copolymer is prepared by using a RAFT reversible addition-fragmentation chain transfer emulsion polymerization method, and the specific steps are as follows:

[0051] Step 1: Dissolve 1 part by mass of an amphiphilic macromolecular reversible addition fragmentation chain transfer agent (RAFT agent) in 10 parts by mass of water, then add different parts by mass of styrene monomer (see Table 1 for details) and stir until the mixture is uniformly mixed, add an aqueous solution of potassium persulfate (0.02 parts by mass of potassium persulfate is dissolved in 12 parts by mass of water in advance) at 70°C, react for 1 hour, and obtain a styrene homopolymer, which is stably dispersed in water in the form of particles to form a latex; wherein the chemical structure of the amphiphilic macromolecular RAFT agent is:

[0052]

[0053] Step 2, after cooling the above latex to room temperature, adding a 10wt% sodium hydroxide aqueous solution to adjust the pH to 8.0 (1 part by mass of sodium hydroxide is dissolved in 10 parts by mass of water), then adding 70 parts by mass of isooctyl acrylate, then adding 60 parts by mass of water, raising the temperature of the reaction system to 45°C, then adding 0.02 parts by mass of azobisisobutylimidazoline hydrochloride, reacting for 4 hours in an anaerobic environment, then adding different parts by mass of styrene (see Table 1 for details), reacting for 4 hours in an anaerobic environment, continuing to add 0.02 parts by mass of azobisisobutylimidazoline hydrochloride, then adding 80 parts by mass of isooctyl acrylate and 30 parts by mass of water, and continuing to react for 5 hours in an anaerobic environment to obtain a tetrablock copolymer latex;

[0054] Step 3, after the reaction is completed, the polymer latex, 30wt% hydrogen peroxide and 7.5wt% hydrochloric acid are placed in a beaker in a volume ratio of 2:1:2, stirred for 15 minutes until uniform, heated to 50°C, and reacted for 3 hours; the precipitated product is then washed with distilled water until neutral, dried, and placed in a vacuum oven at 120°C for 5-20 hours to finally obtain a tetrablock copolymer;

[0055] Step 4, dissolving the tetrablock copolymer in a dispersion medium, coating it in an argon environment to form a film, and drying it at 100° C. for 10 minutes to finally obtain an OCA optical adhesive with a thickness of 25 μm.

[0056] The molecular weight of the polymers was characterized by gel permeation chromatography (GPC) using Waters 1525-2414-717 instrument, with tetrahydrofuran as the eluent and narrow distribution polystyrene standards as the calibration.

[0057] The mechanical properties of the polymer were tested by a universal material testing machine (Zwick / Roll Z020). The polymer film prepared in the fourth step was cut into dumbbell-shaped specimens with a standard cutting knife for later use. The test method adopted GB 16421-1996, the tensile rate was 30 mm / min, and the test of each sample was repeated at least three times.

[0058] The stress relaxation recovery performance of the polymer was tested by DMA (TAQ800). The OCA optical pressure-sensitive adhesive film in the fourth step was cut into strips with a width of 5 mm and a length of 25 mm. The OCA optical pressure-sensitive adhesive was stretched for 1 h at a strain of 100%, 200%, 300%, and 400%, and then maintained at a stress of 0 MPa for 1 h. The recovery data was recorded, and the strain recovery rate was calculated.

[0059] The dynamic mechanical properties of the polymer were characterized by a rotational rheometer (HAAKE MARS 60), the polymer film was cut into circular specimens with a diameter of 2 cm, the test frequency was 0.01 Hz-1 Hz, and the test temperature was 25° C. The loss factor tan δ of the material was recorded during the measurement.

[0060] The peel strength of the polymer was tested by an adhesive shear strength tester (KJ-1066A). The OCA optical pressure-sensitive adhesive film in the fifth step was cut into strips with a width of 25 mm and a length of about 300 mm. The test method adopted GB / T 2792-2014, and the test of each sample was repeated at least three times.

[0061] Table 1 shows the effects of adding different weight portions of styrene on the mechanical properties and peel strength.

[0062]

[0063]

[0064] Figure 1 The GPC curve data of the copolymers obtained after each reaction in Copolymer 1 are shown. From left to right, the first curve is polystyrene (PS); the second curve is poly(styrene-b-isooctyl acrylate) (SEHA); the third curve is poly(styrene-b-isooctyl acrylate-b-styrene) (SEHAS); the fourth curve is poly(styrene-b-isooctyl acrylate-b-styrene-isooctyl acrylate) (SEHASEHA); with the increase of the number of blocks, the molecular weight of the polymer shifts to a high molecular weight as a whole, indicating that the product is a block copolymer. The molecular weight of each segment is 1.5W-18W-1.2W-18W, and the tail segment mainly plays a role in adjusting the modulus of the block copolymer.

[0065] Figure 2The figure shows the mechanical property curve of copolymer 1, from which it can be seen that the polymer has a low modulus of 100.8KPa, a low stress of 0.42MPa and a high elongation at break of nearly 1300%. As can be seen from Table 1, by adjusting the addition amount of M1 and M3, when the molecular weight of the hard segment increases, the Young's modulus also increases, and the peel strength decreases.

[0066] Figure 3 From the strain recovery rate data of the OCA optical pressure-sensitive adhesive prepared from copolymer 1, it can be seen that under a tensile strain of 100%, the strain recovery rate is 95.7%; under a tensile strain of 200%, the strain recovery rate is 97.3%; under a tensile strain of 300%, the strain recovery rate is 96.5%; under a tensile strain of 400%, the final deformation rate is only 96.3%.

[0067] Figure 4 The shear dynamic mechanical properties of the OCA optical pressure-sensitive adhesive prepared from copolymer 1 show that its shear modulus is only 18.1 KPa.

[0068] Figure 5 : is the peel strength data of OCA optical pressure-sensitive adhesive. When the film thickness is 25 μm, the peel strength of the OCA optical pressure-sensitive adhesive film is 8.90 N / 25 mm.

[0069] Example 2: Preparation and properties of poly(styrene-b-isooctyl acrylate-b-styrene-b-isooctyl acrylate) tetrablock copolymer

[0070] This embodiment adopts RAFT reversible addition fragmentation chain transfer emulsion polymerization method to prepare materials, and the specific steps are as follows:

[0071] Step 1, dissolving 1 part by mass of an amphiphilic macromolecular reversible addition-fragmentation chain transfer agent in 10 parts by mass of water, then adding 4 parts by mass of styrene monomer and stirring until uniformly mixed, adding potassium persulfate (0.02 parts by mass of potassium persulfate dissolved in 12 parts by mass of water) at 70° C., reacting for 1.5 hours to obtain a homopolymer, which is stably dispersed in water in the form of particles to form a latex; wherein the chemical structure of the amphiphilic macromolecular RAFT agent is:

[0072]

[0073] Step 2, after cooling the solution to room temperature, adding a 10wt% sodium hydroxide aqueous solution (1 part by mass of sodium hydroxide is dissolved in 20 parts by mass of water) to adjust the pH to 8.0, then adding 70 parts by mass of isooctyl acrylate, then adding 100 parts by mass of water, raising the temperature of the reaction system to 45°C, then adding 0.02 parts by mass of azobisisobutylimidazoline hydrochloride, reacting for 4 hours in an anaerobic environment, then adding 4 parts by mass of styrene, reacting for 4.5 hours in an anaerobic environment, continuing to add 0.02 parts by mass of azobisisobutylimidazoline hydrochloride, and then adding different parts by mass of isooctyl acrylate (see Table 2 for details), and continuing to react for 5.5 hours in an anaerobic environment to obtain a tetrablock copolymer latex;

[0074] Step 3, after the reaction is completed, the polymer latex, 30wt% hydrogen peroxide and 7.5wt% hydrochloric acid are placed in a beaker in a volume ratio of 2:1:2, stirred for 15 minutes until uniform, heated to 50°C, and reacted for 3 hours; the precipitated product is then washed with distilled water until neutral, dried, and placed in a vacuum oven at 120°C for 5-20 hours to finally obtain a tetrablock copolymer;

[0075] Step 4, dissolving the prepared tetrablock copolymer in tetrahydrofuran, coating it in an argon environment to form a film, and drying it at 100° C. for 10 minutes to finally obtain an OCA optical adhesive with a thickness of 25 μm.

[0076] The molecular weight characterization and mechanical property tests of the polymer in this example are similar to those in Example 1.

[0077] Table 2 shows the effect of adding different weight portions of styrene on the mechanical properties and peel strength.

[0078]

[0079]

[0080] The content of M4 is adjusted in Table 2. It can be seen that as the proportion of M4 increases, the modulus of the obtained copolymer becomes lower. However, too high a terminal addition amount will lead to a decrease in the terminal conversion rate, resulting in an increase in economic costs.

[0081] Figure 3 The strain recovery rate data of the OCA optical pressure-sensitive adhesive prepared by copolymer 1 in this embodiment shows that under a tensile strain of 100%, the strain recovery rate is 96.7%; under a tensile strain of 200%, the strain recovery rate is 96.2%; under a tensile strain of 300%, the strain recovery rate is 97.4%; under a tensile strain of 400%, the final deformation rate is only 97.2%.

[0082] Figure 4The shear dynamic mechanical properties of the OCA optical pressure-sensitive adhesive prepared by copolymer 1 in this example show that the shear modulus is only 21.7 KPa. Figure 5 : is the peel strength data of OCA optical pressure-sensitive adhesive. When the film thickness is 25 μm, the peel strength of the OCA optical pressure-sensitive adhesive film is 17.4 N / 25 mm.

[0083] Example 3: Preparation and properties of poly((acrylamide-ran-acrylic acid)-b-(isooctyl acrylate-ran-hydroxyethyl methacrylate)-b-(styrene-ran-acrylic acid)-b-(isooctyl acrylate-ran-hydroxyethyl acrylate)) block copolymer

[0084] This embodiment adopts RAFT reversible addition fragmentation chain transfer emulsion polymerization method to prepare materials, and the specific steps are as follows:

[0085] (1) 1 part by mass of an amphiphilic macromolecular reversible addition-fragmentation chain transfer agent was dissolved in 15 parts by mass of water, and then 4 parts by mass of styrene monomer and 0.03 parts by mass of acrylic acid were added and mixed until uniformly mixed, and potassium persulfate (0.02 parts by mass of potassium persulfate was dissolved in 12 parts by mass of water) was added at 70° C. and reacted for 1.5 hours. At this time, the polymer was stably dispersed in water in the form of particles to form a latex; wherein the chemical structure of the amphiphilic macromolecular RAFT agent is:

[0086]

[0087] (2) After the solution is cooled to room temperature, a 10 wt % sodium hydroxide aqueous solution (1 part by mass of sodium hydroxide is dissolved in 20 parts by mass of water) is added to adjust the pH to 8.0, and then 70 parts by mass of isooctyl acrylate and 10 parts by mass of hydroxyethyl methacrylate are added, and then 70 parts by mass of water are added, and the temperature of the reaction system is raised to 45° C., and then 0.02 parts by mass of azobisisobutylimidazoline hydrochloride is added, and the reaction time is 4 hours in an anaerobic environment, and then 4 parts by mass of styrene and 0.03 parts by mass of acrylic acid are added, and the reaction is carried out in an anaerobic environment for 4.5 hours, and 0.02 parts by mass of azobisisobutylimidazoline hydrochloride is added continuously, and then 70 parts by mass of isooctyl acrylate, 10 parts by mass of hydroxyethyl acrylate and 40 parts by mass of water are added, and the reaction is continued for 5.5 hours in an anaerobic environment to obtain a tetrablock copolymer latex;

[0088] (3) After the reaction is completed, the polymer latex, 30 wt% hydrogen peroxide and 7.5 wt% hydrochloric acid are placed in a beaker in a volume ratio of 2:1:2, stirred for 15 minutes until uniform, heated to 50°C, and reacted for 3 hours; the precipitated product is then washed with distilled water until neutral, dried, and placed in a vacuum oven at 120°C for 5-20 hours to finally obtain a tetrablock copolymer;

[0089] (4) 90 parts by weight of the tetrablock copolymer is dissolved in a dispersion medium, coated into a film in an argon environment, and dried to finally obtain an OCA optical adhesive.

[0090] The molecular weight characterization and mechanical property tests of the polymer in this example are similar to those in Example 1.

[0091] Figure 3 From the strain recovery rate data of the prepared OCA optical pressure-sensitive adhesive, it can be seen that under a tensile strain of 100%, the strain recovery rate is 97.5%; under a tensile strain of 200%, the strain recovery rate is 98.5%; under a tensile strain of 300%, the strain recovery rate is 95.7%; under a tensile strain of 400%, the final deformation rate is only 95.8%.

[0092] Figure 4 The shear dynamic mechanical properties of the prepared OCA optical pressure-sensitive adhesive show that its shear modulus is only 23.8 KPa.

[0093] Figure 5 The peel strength data of the prepared OCA optical pressure-sensitive adhesive is 12.4 N / 25 mm when the film thickness is 25 μm.

[0094] Comparative Example 1: Preparation of an optical pressure-sensitive adhesive of a tetrablock copolymer of poly(styrene-b-isooctyl acrylate-b-styrene-b-isooctyl acrylate), the material was prepared by a RAFT reversible addition-fragmentation chain transfer emulsion polymerization method, and the specific steps are as follows:

[0095] Step 1, dissolving 1 part by mass of an amphiphilic macromolecular reversible addition-fragmentation chain transfer agent in 15 parts by mass of water, then adding 4 parts by mass of styrene monomer and stirring until the mixture is uniformly mixed, adding potassium persulfate (0.02 parts by mass of potassium persulfate dissolved in 12 parts by mass of water) at 70° C., and reacting for 1.5 hours, at which time the polymer is stably dispersed in water in the form of particles to form a latex; wherein the chemical structure of the amphiphilic macromolecular RAFT agent is:

[0096]

[0097] Step 2, after cooling the solution to room temperature, adding a 10wt% sodium hydroxide aqueous solution (1 part by mass of sodium hydroxide is dissolved in 20 parts by mass of water), then adding 40 parts by mass of isooctyl acrylate, and then adding 70 parts by mass of water, raising the temperature of the reaction system to 45°C, then adding 0.02 parts by mass of azobisisobutylimidazoline hydrochloride, reacting for 4 hours in an anaerobic environment, then adding 4 parts by mass of styrene, reacting for 4.5 hours in an anaerobic environment, continuing to add 0.02 parts by mass of azobisisobutylimidazoline hydrochloride, then adding 40 parts by mass of isooctyl acrylate and 40 parts by mass of water, and continuing to react for 5.5 hours in an anaerobic environment to obtain a tetrablock copolymer latex;

[0098] (3) After the reaction is completed, the polymer latex, 30 wt% hydrogen peroxide and 7.5 wt% hydrochloric acid are placed in a beaker in a volume ratio of 2:1:2, stirred for 15 minutes until uniform, heated to 50°C, and reacted for 3 hours; the precipitated product is then washed with distilled water until neutral, dried, and placed in a vacuum oven at 120°C for 5-20 hours to finally obtain a tetrablock copolymer;

[0099] (4) The prepared tetrablock copolymer was dissolved in a dispersion medium, coated into a film in an argon environment, and dried at 100° C. for 10 minutes to finally obtain an OCA optical adhesive with a thickness of 25 μm.

[0100] The molecular weight characterization and mechanical property tests of the polymer in this example are similar to those in Example 1.

[0101] Figure 3 The strain recovery rate data of the prepared OCA optical pressure-sensitive adhesive shows that under 100% tensile strain, the strain recovery rate is 96.3%; under 200% tensile strain, the strain recovery rate is 98.2%; under 300% tensile strain, the strain recovery rate is 95.1%; under 400% tensile strain, the strain recovery rate is 96.3%. The elasticity of the polymer is mainly provided by the hard segment formed by its microphase separation. Figure 4 The shear dynamic mechanical properties of OCA optical pressure-sensitive adhesive are shown in Figure 2, and its shear modulus is only 21.5 Pa. Its low modulus is due to its high proportion of soft segments and terminal free segments. Figure 5 The peel strength data of OCA optical pressure-sensitive adhesive is 14.7N / 25mm when the film thickness is 25μm. The low modulus feature can increase the contact area between the optical adhesive and the adherend, thereby improving its peel strength.

[0102] Comparative Example 2

[0103] Referring to the method of Example 1, the addition of the fourth-stage monomer was reduced to prepare a poly(styrene-b-isooctyl acrylate-b-styrene) triblock copolymer, and the addition of the third and fourth-stage monomers was reduced to prepare a poly(styrene-b-isooctyl acrylate) diblock copolymer. The pressure-sensitive adhesive prepared from the blend was used as a control, and the mass ratio of the triblock copolymer to the diblock copolymer was 50:50.

[0104] Table 3 is a performance comparison of the tetrablock copolymer of Comparative Example 1, the triblock copolymer of Comparative Example 2, and the polymer after the triblock and diblock copolymers are blended. Compared with the triblock copolymer with the same hard segment content, its Young's modulus is reduced from 162.4kPa to 100.8kPa, and the peel strength is also higher. Compared with the design of the triblock copolymer and the diblock copolymer blend, its Young's modulus is also lower. The design of the tetrablock copolymer structure has good low modulus and high elastic properties.

[0105] Table 3 Properties of block copolymers of Comparative Example 1 and Comparative Example 2

[0106]

[0107] The above embodiments are used to illustrate the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.

Claims

1. A low modulus and high elasticity OCA optical pressure-sensitive adhesive, characterized in that: The preparation of the OCA optical pressure-sensitive adhesive comprises the following steps: dissolving raw materials containing a tetrablock copolymer, a tackifying resin and an auxiliary agent in a dispersion medium, coating to form a film and then drying to obtain the obtained product; The general structural formula of the tetrablock copolymer is M1-b-M2-b-M3-b-M4, wherein M1, M2, M3, and M4 are comonomers in the block copolymer, M1 and M3 are from hard monomers, and M2 and M4 are from soft monomers; the mass proportion of the hard monomer in the comonomers is 3-30%, and the mass proportion of the soft monomer is 70-90%; the mass proportion of M4 in the comonomers is greater than 0%.

2. The low modulus and high elasticity OCA optical pressure-sensitive adhesive according to claim 1, characterized in that: The number average molecular weight of the tetrablock copolymer is 80,000-800,000 g / mol, wherein the number average molecular weight of the block formed by M2 is 100,000-200,000 g / mol, and the number average molecular weight of the block formed by M4 is 100,000-200,000 g / mol.

3. The low modulus and high elasticity OCA optical pressure-sensitive adhesive according to claim 1, characterized in that: The hard monomers include one or more of styrene, methyl acrylate, methyl methacrylate, acrylamide, methacrylic acid, acrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, acrylonitrile and vinyl acetate, and the glass transition temperature of the blend is in the range of 60 to 150°C.

4. The low modulus and high elasticity OCA optical pressure-sensitive adhesive according to claim 1, characterized in that: The soft monomer includes one or more of 2-propylheptyl acrylate, octyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, isooctyl acrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, isooctyl methacrylate, butadiene, isoprene, methacrylic acid, acrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, ethylene-butene and methacrylic acid, and the glass transition temperature of the blend ranges from -90 to -30°C.

5. The low modulus and high elasticity OCA optical pressure-sensitive adhesive according to claim 1, characterized in that: In the comonomer, M1 accounts for 2-15% by weight, M2 accounts for 30-90% by weight, M3 accounts for 2-15% by weight, and M4 accounts for more than 0% by weight and less than 60% by weight.

6. The low modulus and high elasticity OCA optical pressure-sensitive adhesive according to claim 1, characterized in that: The tackifying resin includes any one or more of T-801, T-801L, 900L, 901L, TP2019 and 803L; The other additives are any one or more of antioxidants, ultraviolet light absorbers, anti-ultraviolet additives and inks; The dispersion medium includes any one of diethyl ether, methyl tert-butyl ether, tetrahydrofuran, methyl ethyl ketone, ethyl acetate and methyl propionate; In the wavelength range of 300-800nm, the light transmittance of the OCA optical pressure-sensitive adhesive is above 90% and the haze is below 1%.

7. The method for preparing the low modulus and high elasticity OCA optical pressure-sensitive adhesive according to any one of claims 1 to 6, characterized in that: Includes steps: (1) dissolving an amphiphilic macromolecular reversible addition-fragmentation chain transfer agent in water, adding a first monomer, mixing, and then adding a first initiator to react for 1-3 hours to obtain a latex formed by a homopolymer; (2) adjusting the pH of the latex in step 1 to 6.0-12.0, adding the second monomer, water and the second initiator thereto, reacting for 2-6 hours in an anaerobic environment, then adding the first monomer, reacting for 2-6 hours in an anaerobic environment, continuing to add the second initiator and the second monomer, and continuing to react for 2-6 hours in an anaerobic environment to obtain a polymer latex; (3) mixing the polymer latex, hydrogen peroxide and hydrochloric acid for reaction for 1.5-3 hours, washing and drying the precipitated product to obtain a tetrablock copolymer; (4) dissolving the tetrablock copolymer, tackifying resin and auxiliary agent in a dispersion medium, coating to form a film in an inert gas environment, and drying to obtain the OCA optical adhesive.

8. The method for preparing the low modulus and high elasticity OCA optical pressure-sensitive adhesive according to claim 7, characterized in that: The reaction temperature in step 1 is 40-90°C; the reaction temperature in step 2 is 40-60°C; the reaction temperature in step 3 is 40-90°C; In step 3, the hydrogen peroxide is an aqueous solution with a mass concentration of 20-40wt%, the hydrochloric acid is an aqueous solution with a mass concentration of 5-10wt%, and the volume ratio of the polymer latex, the hydrogen peroxide aqueous solution and the hydrochloric acid aqueous solution is 1:(1-5):(1-5).

9. The method for preparing the low modulus and high elasticity OCA optical pressure-sensitive adhesive according to claim 7, characterized in that: The chemical structural formula of the amphiphilic macromolecular reversible addition-fragmentation chain transfer reagent is: R-(X n1 -bY n2 )-Z; wherein R is isopropanoyl, acetic acid, 2-cyanoacetic acid or 2-aminoacetic acid; X n1 In the formula, X is a methacrylic acid monomer or an acrylic acid monomer unit, n1 is the average polymerization degree of X, and n1 ranges from 10 to 30; Y n2 Wherein Y is a styrene monomer, n-butyl acrylate monomer, methyl acrylate, isooctyl acrylate or methyl methacrylate monomer unit, n2 is the average polymerization degree of Y, and n2 ranges from 1 to 8; Z is an alkyl dithioester group or an alkyl trithioester group; and the amount of RAFT agent added is 0.1-1.0wt% of the mass of all copolymerized monomers.

10. The method for preparing the low modulus and high elasticity OCA optical pressure-sensitive adhesive according to claim 7, characterized in that: The first initiator is any one of ammonium persulfate, potassium persulfate, hydrogen peroxide and hydrogen peroxide derivatives; the mass of the first initiator is 1 / 2-1 / 30 of that of the RAFT agent; The second initiator is any one of azobisisobutylimidazoline hydrochloride, azobisisobutylamidine hydrochloride, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, sodium hydrogen persulfate / potassium persulfate redox initiator and sodium persulfate / ammonium persulfate redox initiator, and the mass dosage is 1 / 2-1 / 30 of that of the macromolecular RAFT agent.

Citation Information

Patent Citations

  • High-performance UV curing OCA adhesive and adhesive film

    CN117025136A